O logice i języku naturalnym - V. Koseska-Toszewa (Мовознавство, 2011)
Zakonczona zostala edycja wielotomowej Gramatyki konfrontatywnej bulgarsko-pobkiej (GKBP), na ktörskiada się 12 monografii, oraz Polsko-bulgarskiej gramatyki konfrontatywnej (Synteza GKBP). GKBP i Synteza — to gramatyka konfrontatywna, opracowana na podstawie teorii logicznych. The relationship between logic and natural language is under investigation. It is clamed that the theoretical constructions of mathematical logic is construction are in good agreement with natural language, which is reflected in the interpretation of semantic category of definiteness / indefiniteness as a tool for the quantification of concepts. Understanding the category of definiteness / indefiniteness as a category of sentence follows from the language material (particularly for related language), so that the interpretation of quantification evaluation of predicate becomes a necessity. The paper first proposed to use Petri nets to describe the category of time. The paper stressed that the quantification description of states and events using the formalism of Petri nets reveals the relationship between aspect and time value of the verb, demonstrating redundancy of the interpretation of information about time and aspect separately.